2013
DOI: 10.4236/ajps.2013.46156
|View full text |Cite
|
Sign up to set email alerts
|

<i>Artemisia vulgaris</i> L. Chemotypes

Abstract: Artemisia vulgaris L. was collected from various regions in the USA and Montreal Canada. Gas Chromatography-Mass Spectrometry was used to identify the analytes present in the volatiles extracted by headspace solid-phase microextraction of the crushed leaves and flowers. Four distinct chemotypes are were found: One featuring the coexistence of ar-curcumene and α-zingiberene; two marked by the presence or absence of thujone and santolinatriene; and a fourth characterized by the presence of crysanthenyl acetate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…The plant identity was confirmed by Dr. Marlene Cross, Department of Biology, Mercyhurst University, and a reference voucher specimen (Reference number: TREC He- 00818) was deposited in the Herbarium of the Tom Ridge Center, Erie, Pennsylvania [23]. In addition, the identity of the same plant used in this study was further confirmed using DNA sequencing as recently described by [28]. The leaves and buds (before flowering) were washed, separated and dried before further analysis.…”
Section: Methodsmentioning
confidence: 74%
“…The plant identity was confirmed by Dr. Marlene Cross, Department of Biology, Mercyhurst University, and a reference voucher specimen (Reference number: TREC He- 00818) was deposited in the Herbarium of the Tom Ridge Center, Erie, Pennsylvania [23]. In addition, the identity of the same plant used in this study was further confirmed using DNA sequencing as recently described by [28]. The leaves and buds (before flowering) were washed, separated and dried before further analysis.…”
Section: Methodsmentioning
confidence: 74%
“…The main composition of oil 32 was as follows: cis ‐chrysanthenyl acetate (10.4%), germacrene D (9.5%), and trans ‐thujone (9.4%). Thujone has been determined among main constituents in numerous mugwort oils form the plants growing in Croatia, France, Lithuania, Serbia, the USA, India, Nepal, Turkey, Egypt, and Morocco …”
Section: Resultsmentioning
confidence: 99%
“…Aerial parts Syria [28] a-Thujone (56.1), [16] Caryophyllene (24.1), b-cubebene (12.0), b-elemene (6.0) var. indica Maxim, leaves Vietnam [5] cis-Chrysanthenyl acetate (39.6), p-cymene (17.2), b-phellandrene (11.4), trans-2-hexenal (5.0) Aerial parts Canada (Montreal) [33] Caryophyllene oxide ( Aerial parts, leaf and bud oils the USA (Pennsylvania, Erie) [30] a-Thujone (≤24.3), b-caryophyllene (≤17.5), santolina triene (10.0),…”
Section: Aerial Partsmentioning
confidence: 99%
See 2 more Smart Citations